2004
DOI: 10.1002/bies.20055
|View full text |Cite
|
Sign up to set email alerts
|

Growth and specification: fly Pax6 homologs eyegone and eyeless have distinct functions

Abstract: Development requires not only the correct specification of organs and cell types in the right places (pattern), but also the control of their size and shape (growth). Many signaling pathways control both pattern and growth and how these two are distinguished has been something of a mystery. In the fly eye, a Pax6 homolog (eyeless) controls eye specification together with several other genes. Now Dominguez et al.1 show that Notch signaling controls eye growth through a second Pax6 protein (Eyegone). In mice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…There is evidence that Pax6 and Pax6(5a) have different functions in vivo in both vertebrates [9-11] and invertebrates [12,13]. Studies of Pax6 - and Pax6(5a) -related genes in Drosophila melanogaster , ey/ toy and eyg/ toe , have shown that they promote, respectively, differentiation and proliferation of eye precursor cells [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that Pax6 and Pax6(5a) have different functions in vivo in both vertebrates [9-11] and invertebrates [12,13]. Studies of Pax6 - and Pax6(5a) -related genes in Drosophila melanogaster , ey/ toy and eyg/ toe , have shown that they promote, respectively, differentiation and proliferation of eye precursor cells [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Studies of Pax6 - and Pax6(5a) -related genes in Drosophila melanogaster , ey/ toy and eyg/ toe , have shown that they promote, respectively, differentiation and proliferation of eye precursor cells [12,13]. Overexpression of Pax6 and Pax6(5a) can alter the expression of different sets of genes in mammals [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the PAX6 orthologs Twin of eyeless (TOY) and Eyeless (EY), two Drosophila Pax6-like genes not found in vertebrates [eyegone (eyg) and twin-of-eyegone (toe)] may act in parallel to ey during eye formation (Jang et al, 2003). Recent results suggest EY and EYG play discrete, but coordinated, roles, with EY providing important eye-specification cues and EYG regulating eye growth (Dominguez et al, 2004) (reviewed by Rodrigues and Moses, 2004).…”
Section: Box 1 Eyegone and Eyeless: Insights Into Pax6-mediated Coormentioning
confidence: 99%
“…The inability to detect homologs in various well‐curated genomes of basal chordates and vertebrates suggests that eyg was lost during the early evolution of chordates. Noting the absence of eyg in vertebrates, it has been previously proposed that Drosophila eyg might be evolutionarily related to isoform 5a of vertebrate Pax6 (Jun et al, '98; Rodrigues and Moses, 2004; Yao and Sun, 2005). In the latter case, the PAI subdomain is assumed to be rendered nonfunctional by the insertion of 14 amino acids encoded on the differentially spliced exon (Epstein et al, '94).…”
Section: Resultsmentioning
confidence: 99%